Monitoring the Activation of Copper-Containing Zeotype Catalysts Prepared by Direct Synthesis Using in Situ Synchrotron Infrared Microcrystal Spectroscopy and Complementary Techniques - Eschenroeder, Eike C. V. (2014)
The use of copper polyamine complexes as structure directing agents for microporous solids offers a direct route to the inclusion of Cu2+ complex cations in their pores: upon calcination, this gives active catalysts for the selective catalytic reduction of NO with NH3. In situ synchrotron IR absorption spectroscopy on crystals of dimensions 25-35 μm has been used to monitor the dehydration of the Cu2+-cyclam complex that acts as a cotemplate for the silicoaluminophosphate SAPO STA-7 and, at higher temperatures (400 C), the calcination that gives the active catalyst Cu,H-SAPO STA-7. Polarized synchrotron IR microspectroscopy reveals strong alignment of N-H bonds of the Cu2+ cyclam in the larger cages of as-prepared STA-7, and complementary X-ray diffraction, ESR, UV-visible spectroscopy, and computer simulation indicate that the hydrated complex acts as cotemplate during crystallization: dehydration leads to removal of its coordinated water by 200 C.